Microfinance as a life quality improvement tool in the post-crisis period of the economy of Kazakhstan (Journal of Economic Research & Business Administration, 2022)
This article extends research about the impact of microfinance on macroeconomic performance, includingeconomic and financial development. Microfinance, as emphasized by the Asian DevelopmentBank, provides financial services to the poor, thus increasing the level of consumer activity, productionand entrepreneurship, making a significant contribution to the development of the economy, especiallyin post-crisis periods. Stable economic growth, as proved by developed and developing countries, directlydepends on the activity of small and medium-sized enterprises, which stimulate the entrepreneurialactivity of population and creates new jobs. However, one of the significant obstacles to the creationand development of SMEs is access to finance.The purpose of this paper is to analyze the impact of SME financing, both through microfinance organizationsand through banks, on the Human Development Index, as an indicator of the development of the economy of Kazakhstan. This index is a more comprehensive indicator of a country’s development,which takes into account not only economic growth, but also the quality of life of population. The paperalso discusses the relationship between SME financing and the proportion of the country’s populationwith incomes below the subsistence level. Thus, given the narrow focus of microfinance on the poor, anumber of studies have found that this sector contributes to the poverty reduction.For the current study, two multiple linear regression models were constructed. Analysis of the resultsshowed that SME lending has a positive effect on the socio-economic development of Kazakhstan.However, the results also showed that as the proportion of poor people increases, the level of bank lendingdecreases, while the level of MFI lending increases. Thus, MFIs continue to lend to the economy ofKazakhstan, even despite the decrease in the solvency of entrepreneurs, which is fully consistent withthe concept of microfinance. Thus, there is a need for the full inclusion of MFIs in the country’s financialsystem, as well as the expansion of financial services provided by these organizations.Key words: microfinance, microfinance organizations, entrepreneurship, small and medium business(SME), lending, human development index (HDI), poverty index.